2017
DOI: 10.1038/modpathol.2017.43
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of tumor-infiltrating lymphocyte and tertiary lymphoid structure assessment in human breast cancer

Abstract: The presence of tumor-infiltrating lymphocytes (TIL), reflecting host immune activity, is frequently correlated with better clinical outcomes, particularly in HER2-positive and triple-negative breast cancer. Recent findings suggest that organization of immune infiltrates in tertiary lymphoid structures also has a beneficial effect on survival. This study investigated inter- and intra-observer variation in TIL assessment using conventional hematoxylin-eosin versus immunohistochemical staining to identify immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 25 publications
5
99
3
Order By: Relevance
“…Additionally, our data showed that CD3+, CD8+, FOXP3+, CD20+ and CD68+ cells were positively correlated with AV‐TILs percentage, and that TILs were higher in the more aggressive TNBC subtype than in other subtypes. It has been reported that TILs assessed in H&E‐stained sections are significantly correlated with CD20 and CD45 positivity in BC . The high‐CD8+ and high‐CD3+ cellular infiltrate showed good prognostic and independent predictive value in TNBC regardless of other clinicopathological parameters.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, our data showed that CD3+, CD8+, FOXP3+, CD20+ and CD68+ cells were positively correlated with AV‐TILs percentage, and that TILs were higher in the more aggressive TNBC subtype than in other subtypes. It has been reported that TILs assessed in H&E‐stained sections are significantly correlated with CD20 and CD45 positivity in BC . The high‐CD8+ and high‐CD3+ cellular infiltrate showed good prognostic and independent predictive value in TNBC regardless of other clinicopathological parameters.…”
Section: Discussionmentioning
confidence: 89%
“…The importance of tertiary lymphoid structures, which represent an organized immune infiltrate with all the features of a lymph node to facilitate antigen presentation, lymphocyte education and effector cell proliferation, has been described in different tumor types [13]. A recent study suggests that IHC is required to reliably identify tertiary lymphoid structures [84], however consensus on the most appropriate marker or combination of markers for this task is not yet apparent. Whether further descriptive analysis of the immune infiltrate in tumors, incorporating features such as the density and distribution of TILs, organization into tertiary lymphoid structures, or the presence of hotspots, adds prognostic information to an overall TILs assessment remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…ICC improved to 0.89 (95% CI 0.85–0.92) and it was suggested that visual reference tools such as the software used in this study might be of value both in research and in clinical practice [14,52]. A recent study has shown similarly high inter-observer and intra-observer ICC for scoring TILs in invasive breast carcinoma, however it was noted that agreement for the iTILs scores was lower than for the sTILs scores [84]. There were no significant differences between the inter- and intra-observer ICC values when scoring H&E sections or IHC stained sections, and concordance between H&E and IHC scores was high (ICC 0.75 for iTIL and ICC 0.84 for sTIL) [84].…”
Section: Tils In Invasive Breast Carcinomamentioning
confidence: 92%
See 2 more Smart Citations